Observation of Ocean Winds Using Satellite-based GNSS+R Technology - Song, Yunyi (Transactions on Environment, Energy and Earth Sciences, 2024)
In recent years, due to climate change, there has been a significant increase in sea surface winds, leading to multiple iterations of satellite-based GNSS+R (Global Navigation Satellite System Reflectometry). The offshore wind measurement technology utilizing GNSS+R offers continuous and widespread capabilities. GNSS+R reflected signals have been extensively researched internationally for typhoon detection and disaster prediction applications. Despite its emerging nature, there is a lack of comprehensive articles detailing the development history of GNSS+R. Therefore, this paper aims to thoroughly review GNSS+R’s evolution by examining the connection between signals from surface mirror reflection and sea surface wind. Starting with the principles of ocean surface wind measurement proposed by NASA in 1997, the introduction of the Z-V model, and the advancement of GNSS+R remote sensing techniques, such as BP neural network-based GNSS+R sea surface wind speed retrieval methods, this paper traces the significant advancements in inversion technologies. It also discusses the international development of GNSS+R for offshore wind measurement, from the initial concept to the widespread applications of projects such as the UK’s Surrey company, the European Space Agency’s GEROS program, and NASA’s CYGNSS. Additionally, the paper covers the domestic launches of the Wind Catcher-1A and 1B satellites and the application of BeiDou navigation satellites. It summarizes the future technological advancements in GNSS+R remote sensing both domestically and internationally, exploring its potential for acquiring sea surface wind field information and predicting flood disasters. Finally, it emphasizes the challenges of signal interference and inversion algorithm accuracy with the hope of overcoming these technical hurdles.